Genetic diversity of wild populations of Tuberaria major (Cistaceae), an endangered species endemic to the Algarve region (Portugal), using ISSR markers - Trindade, Helena (2013)
Tuberaria major (Willk.) P. Silva & Rozeira (Cistaceae) is an endangered species endemic to the Algarve region (Portugal). Due to the increasing urban pressure, natural populations are now reduced to small nuclei located in the center of the region. Genetic variation within and among three populations of this species was evaluated using inter-simple sequence repeat (ISSR) markers. A total of eight primers generated 128 well defined bands, with an average of 16 bands per primer. At the population level, the percentage of polymorphic bands ranged from 55 to 73%, while at the species level this value increased to 98%. The population showing the highest genetic variability was Olhão and the lowest was Gambelas. According to the cluster analysis based on UPGMA, the population Gambelas was clearly separated from the other two, which clustered together. The three populations revealed a high level of genetic diversity, with a Nei’s genetic diversity of 0.197 and Shannon’s diversity index of 0.324. A high level of gene flow was observed among populations (Nm ¼ 2.199), reflecting a moderate level of genetic differentiation (GST ¼ 0.185), and no correlation between genetic and geographical distances (r ¼ 1.000;P > 0.05). Based on the results obtained it is concluded that the Gambelas population should be a priority for conservation, including the ex situ propagation and restoration.